Penerapan Model Project Based Learning (PjBL) untuk Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik Kelas IV pada Mata Pelajaran IPAS Di SDN 40 Mataram - Supriyadin, Iwan; Asrin; Mardiana, Nana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Learning Natural and Social Sciences (IPAS) in elementary school plays an important role in developing students’ scientific and social thinking skills. However, classroom observations indicate that students tend to be passive and are not accustomed to thinking critically. Low participation in learning activities and difficulty connecting IPAS concepts with everyday phenomena have contributed to low learning outcomes and weak critical thinking skills, highlighting the need for more active, meaningful, and contextual learning innovations. One model aligned with the demands of the Kurikulum Merdeka is Project-Based Learning (PjBL), which emphasizes learning through real project completion to develop knowledge, skills, and attitudes in an integrated manner. Initial observations in Grade IV at SDN 40 Mataram showed that out of 13 students, only 4 students (30%) achieved scores above the Minimum Mastery Criteria (KKM). These low outcomes were largely due to the conventional, teacher-centered learning approach. Therefore, this study aims to improve students’ critical thinking skills and learning outcomes through the implementation of the Project-Based Learning (PjBL) model in IPAS instruction. This research employed a Classroom Action Research (CAR) approach using the Kemmis & McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through student activity observations and learning outcome tests. The findings show that the achievement of PjBL syntax increased from 73% in Cycle I to 87% in Cycle II. Students’ critical thinking skills also improved from an average of 60% in the pre-cycle to 75% in Cycle I and 86% in Cycle II, while learning mastery increased from 30% to 85%. Thus, the implementation of the Project-Based Learning model proved effective in enhancing students’ critical thinking skills and learning outcomes in IPAS learning at SDN 40 Mataram.